The study of reading comprehension in English as a Foreign Language in the current educational context (Research, Society and Development, 2024)
Teaching and learning English as a foreign language requires more attention within society each day. Consequently, the reflections surrounding said language and its related aspects are continuously increasing. This review paper seeks to study the research of strengthening reading comprehension in English. Therefore, several databases, open and closed, institutional repositories, and books are researched through documentary analysis, resulting in identifying several ways to conceptualize reading comprehension and its strengthening in the English area in different educational levels that have existed in the past years. However, reading stands out in studies as a cognitive process that transcends translation. Lastly, it is concluded that reading, as a multidimensional reality in which various elements intervene, implies changes in the didactic perspective reflected in the way of approaching it within the education system to enhance its acquisition and reach the benefits it offers.